IoT-Based kWh Monitoring Prototype Using PZEM-004T Sensor and NodeMCU ESP8266 Microcontroller: A Comprehensive Experimental Evaluation - Nuraji Permana Putra (Journal of Emerging Innovations in Engineering, 2025)
This study presents experimental validation of an IoT-based household energy monitoring system using PZEM-004T sensor and NodeMCU ESP8266 microcontroller. Twenty testing scenarios were conducted across 10 common household appliances with power specifications ranging from 5W to 561.3W using quantitative R&D methodology. Results demonstrated superior measurement accuracy with 45% of tests achieving ≤5% deviation and 15.8% average deviation compared to nameplate specifications, significantly outperforming conventional clamp meters (31.6% deviation). The system achieved 100% data completeness with sub-2-second latency under stable Wi-Fi conditions, validating IoT reliability for continuous monitoring. Experimental data verified Ohm's Law relationships with strong current-power correlation (r ≈ 0.99). Critical accuracy factors were identified: measurement timing during transient versus steady-state operation (40% of high deviations), worn equipment conditions (30%), and operational mode variations. The PZEM-004T demonstrated robust performance across resistive, inductive, and electronic loads, effectively handling non-sinusoidal waveforms from modern appliances. Integrated real-time cost calculation provided economically meaningful feedback for energy management. Findings confirm that PZEM-004T-based IoT monitoring offers a practical, accurate, and economically viable solution for residential energy management, particularly suitable for developing markets where energy efficiency and cost management are critical concerns.